Homeschooling Is Not Just About Education: Focuses of Meaning. Issue 1 (2nd January 2017) - Neuman, Ari; Guterman, Oz
ABSTRACT: This article explores the meanings parents attribute to homeschooling. The literature reveals two main approaches to this subject: a view of homeschooling as a pedagogical practice and a holistic perspective. Employing qualitative methodologies, we administered in-depth interviews to 30 mothers who engaged in homeschooling in Israel, in order to gain a better understanding of what homeschooling meant to them. Analysis of the interviews indicated that the participants attributed diverse meanings to homeschooling. These represented many themes, which were gathered into four super-themes: control, lifestyle, family, and child. The first two themes were emphasized more often than the latter two.